(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The objective of the research is to identify the auditor’s compliance with the duties and responsibilities assigned to him and the extent to which this affects the quality of the audit. The results showed that the high level of auditors’ awareness of their responsibilities when auditing the accounts of the economic unit, which is mandated to audit their accounts, can contribute strongly to improve audit quality The study showed that the high level of awareness of banks in the sample of the study of the importance of transparency in the presentation of financial statements can contribute to show the results of the audit in a better quality if the data is not presented As well as auditors’ compliance with auditing regulations and instructions, contribute significantly to improving the quality of audit, and it is possible to benefit from the auditor’s sense of responsibility in exerting pressure on the various economic units in order to increase the transparency of their various accounts. This is demonstrated by the analysis of correlation and impact relationships